Heating efficiency dependency on size and morphology of magnetite nanoparticles - Parekh, Kinnari (2018)
Different size magnetite nanoparticles ranging from superparamagnetic (9 nm) to single domain (27 nm) and multi domain (53 nm) were synthesized using chemical route. Morphology of these particles as seen from TEM images indicates shape change from spherical to cubic with the growth of particles. The saturation magnetization (σs) and Specific Loss Power (SLP) showed maximum for single domain size, 72 emu/g and 102 W/g, respectively then those of multi domain size particles. These samples show higher SLP at relatively low concentration, low frequency and low amplitude compared to samples prepared by other routes.